The Hand of Chaos : A Death Gate Novel - Weis, Margaret and Hickman, Tracy (New York Bantam Books, 1993)
Haplo returns to the Lord of the Nexus, only to be sent once again to Arianus, the Realm of the Sky. As the war between humans, elves and dwarves seems imminent, Haplo must choose between obeying the master who rescued him from the deadly Labyrinth, and betraying the powerful Patryn.
Keywords: Magic -- Fiction -- Death Gate Universe (Imaginary place) -- Fiction -- Dragons -- Fiction